Cidades e Mudanças Climáticas no Brasil:: Planejamento de Medidas ou Estado de Risco? - Machado de Mello Bueno, Laura (Sustainability in Debate, 2011)
This paper shows a study of federal bylaws on Climate Change (CC) and on public policies related to urban areas. We aim to analyze the federal bylaws and the institutional frameworks that manage several public policies directly related to CC and cities, although managed by different institutions. Policies related to housing, sanitation, and garbage management are scrutinized, looking for integration indicators proposals. Sectorial visions, including related to environmental, and climate change policies are noted. The urban areas, despite the high grade of urbanization of Brazilian population, and considered vulnerable areas, are not focused. This study is integrated in a broader, on going research “Adaptation to Climate Change and environmental justice: potentials and conflicts in urban environment”.